Hydrophobic ion pairing and microfluidic nanoprecipitation enable efficient nanoformulation of a small molecule indolamine 2, 3‐dioxygenase inhibitor immunotherapeutic - Parisa Badiee; Michelle F. Maritz; Pouya Dehghankelishadi; Nicole Dmochowska; Benjamin Thierry (Wiley, 2024)
Abstract Blockade of programmed cell death‐1 (PD‐1) is a transformative immunotherapy. However, only a fraction of patients benefit, and there is a critical need for broad‐spectrum checkpoint inhibition approaches that both enhance the recruitment of cytotoxic immune cells in cold tumors and target resistance pathways. Indoleamine 2, 3‐dioxygenase (IDO) small molecule inhibitors are promising but suboptimal tumor bioavailability and dose‐limiting toxicity have limited therapeutic benefits in clinical trials. This study reports on a nanoformulation of the IDO inhibitor navoximod within polymeric nanoparticles prepared using a high‐throughput microfluidic mixing device. Hydrophobic ion pairing addresses the challenging physicochemical properties of navoximod, yielding remarkably high loading (>10%). The nanoformulation efficiently inhibits IDO and, in synergy with PD‐1 antibodies improves the anti‐cancer cytotoxicity of T‐cells, in vitro and in vivo. This study provides new insight into the IDO and PD‐1 inhibitors synergy and validates hydrophobic ion pairing as a simple and clinically scalable formulation approach.